1995
DOI: 10.1016/0378-1097(95)00191-7
|View full text |Cite
|
Sign up to set email alerts
|

Buffering capacity and H membrane conductance of Gram-negative bacteria

Abstract: Buffering capacity and membrane H+ conductance were examined in seven Gram-negative species: Aquaspirillum serpens, Pseudomonas aeruginosa, Alcaligenes faecalis, Escherichia coli, Salmonella typhimurium, Proteus mirabilis and Aeromonas hydrophila. All strains of Enterobacteriaceae studied here showed a decrease in both parameters as the external pH increased, over the pH range studied. The other four species presented an increase in buffering capacity and membrane conductance to protons as the external pH incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Gross estimates based on Ohm's law indicated that the resistance of the cell membrane to protons declined as protonmotive force increased, allowing faster rates of ATP hydrolysis and proton pumping. However, proton flux rates predicted by these calculations were 20-50-fold faster than values previously measured in bacteria (Maloney, 1979 ;Rius & Lore! n, 1998 ;Rius et al, 1994 ;Bender et al, 1986).…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…Gross estimates based on Ohm's law indicated that the resistance of the cell membrane to protons declined as protonmotive force increased, allowing faster rates of ATP hydrolysis and proton pumping. However, proton flux rates predicted by these calculations were 20-50-fold faster than values previously measured in bacteria (Maloney, 1979 ;Rius & Lore! n, 1998 ;Rius et al, 1994 ;Bender et al, 1986).…”
Section: Introductionmentioning
confidence: 56%
“…Other lactic acid bacteria had non-growth ATP hydrolysis at rates comparable to those estimated for S. bovis (Rosenberger & Elsden, 1960 ;Fordyce et al, 1984), but direct measurements of proton conductance could not explain these high rates of ATP turnover (Maloney, 1979 ;Rius & Lore! n, 1998 ;Rius et al, 1994 ;Bender et al, 1986).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…While an increase in proton permeability as observed for thermophilic bacilli (1) could provide a plausible explanation for the lowered ⌬pH values, this remains to be experimentally proven with thermophilic alkaliphiles. It should be noted that the proton permeability of the alkaliphile B. alcalophilus is comparable to that of neutrophilic bacteria (23). Moreover, alkaliphilic bacilli have been shown to have appreciable amounts of squalene, squalene derivatives, and C 40 isoprenoids among their neutral membrane lipids, which may prevent proton leakage (2).…”
Section: Resultsmentioning
confidence: 99%